Inhibitory effects of CaO/Fe2O3 on arsenic emission during sewage sludge pyrolysis. (October 2016) - Han, Hengda; Hu, Song; Lu, Chaofeng; Wang, Yi; Jiang, Long; Xiang, Jun; Su, Sheng
Graphical abstract: Highlights: 24.8–63.1% of arsenic escaped from sludge during pyrolysis from 723 to 1123 K. Both CaO and Fe2 O3 could inhibit the emission of arsenic during sludge pyrolysis. CaO could react with As2 O3, As2 S3 and arsenites to form nonvolatile substances. Fe2 O3 could react with NaAsO2 to generate substances stable below 1123 K. Abstract: This work aimed to investigate effects and reaction mechanisms of CaO/Fe2 O3 on emission behaviors of arsenic during sewage sludge pyrolysis. The results showed that 24.8–54.2%, 26.4–60.4% and 27.7–63.1% of arsenic escaped from three samples when pyrolysis process happened at 723, 923 and 1123 K respectively. And the sludge which contained higher calcium and iron contents released less arsenic than others. External CaO and Fe2 O3 were added into the sewage sludge to study their effects on arsenic emissions during pyrolysis, where both of them inhibited arsenic emission effectively, especially at high temperatures. With the help of thermogravimetry analysis and X-ray fluorescence, inhibitory mechanisms of CaO/Fe2 O3 on arsenic emission during sewage sludge pyrolysis were studied. CaO could react with As2 O3, As2 S3 and NaAsO2 to form nonvolatile substances, such as Ca(AsO2 )2 ; while Fe2 O3 could react with NaAsO2 to generate certain substances which was stable below 1123 K.